Dietary diversity practice and its influencing factors among pregnant women in Afar region of Ethiopia: mixed method study - Temesgen Gebeyehu Wondmeneh (BMC, 2022)
Abstract Background Pregnancy can aggravate nutritional deficiencies, especially micronutrient deficiencies, which can have major health impact for the fetus and mother. Women in low-income countries are frequently malnourished when they become pregnant. Identifying the magnitude of dietary diversity and its influencing factors among pregnant women in the pastoral region of Afar, where no study has been conducted, is critical for establishing an intervention program in the region. Method A mixed study comprising 241 pregnant women and six focus group discussions was conducted from October 1 to November 10, 2018. Participants in the quantitative study were selected by a systematic sampling method, whereas those in the focus group discussions were selected by a purposive sampling method. The data were collected using pretested questionnaires administered via face-to-face interviews. Logistic regression determines the association between the dietary diversity practice and its influencing factors. The results were presented by the odds ratio with a 95% confidence interval. A P-value of < 0.05 is used to declare a statistically significant. A thematic framework was used to analyze the qualitative data. Results Seventy-three percent of pregnant women had poor dietary diversity. Dietary diversity was higher in younger pregnant women who were under the age of 20 years (AOR = 5.8; at 95% CI: 1.6-13.5) and aged between 21 and 25 years (AOR = 3.9; at 95% CI: 1.1-12.2) than those pregnant women over the age of 30 years. Those participants with a high average family income (above 4500 birr) had good dietary diversity compared to those with an average family income of less than 1500 birr (AOR = 0.1: 95% CI; 0.02-0.7) and 1500-3000 birr (AOR = 0.05: 95% CI; 0.01-0.2). Pregnant women who had one antenatal care visit had less dietary diversity practice than those who had four or more antenatal care visits (AOR = 0.18: 95% CI; 0.04-0.8). Protein-rich foods (meat and eggs), cereal-based semi-solid foods (porridge and soup), milk, bananas and cabbage, were the most commonly tabooed foods during pregnancy. Protein-rich foods were thought to increase the size of the fetus. Semi-solid foods (porridge and soup), bananas, and cabbage, on the other hand, were thought to stick to the fetus's body. Conclusion Most of the study participants had poor dietary diversity. Older women have lower dietary diversity practices than younger women. Pregnant women with a low family income and only one prenatal care visit were less likely to practice dietary diversity than pregnant women with a high family income and those with four or more antenatal care visits. Pregnant women practiced food taboos due to misconceptions that were producing large babies and attached to the babies' bodies. A public health campaign emphasizing the necessity of antenatal care follow-ups should be launched. Community nutrition education should be provided to reduce the traditional beliefs about certain foods, especially for older women.